Exploring Factors and Intervention Strategies for Eating Disorders in Dancers : A Gut-Brain Axis Perspective (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Exploring Factors and Intervention Strategies for Eating Disorders in Dancers : A Gut-Brain Axis Perspective